The ghost of Blackwood Hall. - Keene, Carolyn (Keene, Carolyn. Nancy Drew mystery stories, 1967)
A search for stolen jewelry takes Nancy to New Orleans where she uncovers a swindling racket in which a medium uses her trade to relieve victims of their valuables.